Contact Dermatitis And Risk Factors Cross Sectional Study on Employees of PT Perkebunan Nusantara 1 Langsa, in Aceh, 2022 - Aulia Zikra; Otniel Ketaren; Janno Sinaga (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Contact dermatitis is often associated with work and is also referred to as occupational contact dermatitis. About 90% of occupational dermatitis is contact dermatitis. This disease attacks workers who are often exposed to toxic or allergic substances, including workers in the agricultural and plantation sectors. The process of planting oil palm seeds until the harvest stage causes workers to be exposed to many chemicals in the form of pesticides, which is one of the causes of occupational skin diseases. This study aims to analyze how high the incidence of contact dermatitis is and what the risk factors are among employees of PT Perkebunan Nusantara 1 Langsa. This study is a quantitative research with a cross sectional design. The population in this study was all 47 employees of Afdelling 1 PTP Nusantara 1 Langsa, and the research sample was used as total sampling. Data collection was carried out directly by distributing observations and distributing questionnaires to employees. Then, continue with the data analysis process using the Chi Square test and logistic regression. The results showed that there were length of work (p=0.000, PR=3.4; 95% CI 2.201-5.294), use of PPE (p=0.006, PR=2.6; 95% CI 1.197-5.676), personal hygiene ( p=0.000, PR=5.2; 95% CI 1.816-14.906) and family history of allergies (p=0.000, PR=3.2; 95% CI 1.615-6.430) against contact dermatitis. Furthermore, the dominant factors related to the incidence of contact dermatitis through the binary logistic regression test were the variables length of work and personal hygiene, where length of work increased the risk of contact dermatitis 7 times and personal hygiene increased the risk of contact dermatitis 6 times.